A dual-photoelectrode photofuel cell based self-powered aptasensor using a multimeter as a direct visual readout strategy. Issue 48 (24th May 2021) - Zhang, Meng; Zhang, Zhenzhen; Wei, Jie; Dai, Zhen; Hao, Nan; Wang, Kun
Abstract : Schematic illustration of the dual-photoelectrode photofuel cell typed self-powered aptasensor for SMZ detection combined with digital multimeter as the direct visual readout strategy. Abstract : A self-powered aptasensor based on a dual-photoelectrode photofuel cell, whose maximum power density and open circuit potential respectively reached 10.77 μW cm −2 and 0.664 V, was proposed combined with a digital multimeter as a direct visual readout strategy, providing a meaningful perspective for miniaturized, implantable, and on-site sensors.